1996
DOI: 10.1017/s0022215100134516
|View full text |Cite
|
Sign up to set email alerts
|

Incidental paranasal sinus inflammatory changes in a British population

Abstract: A retrospective study was carried out to determine the prevalence of abnormality in the paranasal sinuses in a British population having magnetic resonance imaging (MRI) scans for neurological signs and symptoms. The T2-weighted scans of 130 patients were studied. Abnormalities in the paranasal sinuses show as high signal on the T2-weighted scans and thus are clearly seen. Abnormalities included mucosal thickening, fluid levels, sinus opacification and retention cysts/polyps. Of the patients studied, 49.2 per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 14 publications
4
48
0
2
Order By: Relevance
“…CBCT as a new 3D imaging modality could be of a great clinical value not only in screening, but also in planning paranasal surgery. Some of the studies reported on the useful application of CBCT for intraoperative imaging of the paranasal sinus [24,25]. The development of CBCT equipment has resulted in better image quality for diagnoses, exposure to lower radiation doses, easier operation and lower cost than CT and maxillary sinus abnormalities can be demonstrated easily on the CBCT images.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT as a new 3D imaging modality could be of a great clinical value not only in screening, but also in planning paranasal surgery. Some of the studies reported on the useful application of CBCT for intraoperative imaging of the paranasal sinus [24,25]. The development of CBCT equipment has resulted in better image quality for diagnoses, exposure to lower radiation doses, easier operation and lower cost than CT and maxillary sinus abnormalities can be demonstrated easily on the CBCT images.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study using 20 fresh cadavers, Pommer and et al (14) found a mean thickness value of 0.09 AE 0.05 mm (range, 0.02-0.35 mm). In a study analyzing sinus biopsies (6) or magnetic resonance imaging (16). The mucosa could be seen only at a thickness of 2 mm or above, and, therefore, historically, 2 mm was considered a reliable threshold for pathological mucosal swelling (9).…”
Section: Discussionmentioning
confidence: 99%
“…По мнению разных авторов, поражение околоносовых пазух у пациентов с РС наблюдается до 69,5%, в то время как в ряде публи-каций отмечается, что частота встречаемости кли-нических вирусных инфекций ниже, чем в кон-трольных группах. В этих исследованиях у больных РС использовались клинические критерии для уста-новления диагноза синусита, в нашей работе мы об-ратились к помощи МРТ, что помогло оценить ха-рактер и локализацию патологического процесса в околоносовых пазухах [3][4][5][6][7].…”
Section: результаты и обсуждениеunclassified